2021
DOI: 10.1186/s12903-021-01740-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of 25-hydroxyvitamin-D3 and vitamin D receptor gene in human periodontal ligament fibroblasts as response to orthodontic compressive strain: an in vitro study

Abstract: Background This study aimed to investigate, if different physiological concentrations of vitamin D (25(OH)D3) and single nucleotide polymorphisms in vitamin D receptor (VDR) gene have an impact on gene expression in human periodontal ligament (hPDL) fibroblasts induced by simulated orthodontic compressive strain. Methods A pool of hPDL fibroblasts was treated in absence or presence of 25(OH)D3 in 3 different concentrations (10, 40 and 60 ng/ml). I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 53 publications
(97 reference statements)
3
16
1
Order By: Relevance
“…In this study, we found that the serum 25(OH)D level of patients with sepsis was significantly lower than that of the control group, and the VDR rs739837 G > T allelic variation was correlated with the increase of serum 25(OH)D. Küchler et al 24 found that the VDR mRNA expression level in samples of GG genotype in rs739837 was lower, which was consistent with the results of this study. 25(OH)D levels are closely related to neonatal sepsis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we found that the serum 25(OH)D level of patients with sepsis was significantly lower than that of the control group, and the VDR rs739837 G > T allelic variation was correlated with the increase of serum 25(OH)D. Küchler et al 24 found that the VDR mRNA expression level in samples of GG genotype in rs739837 was lower, which was consistent with the results of this study. 25(OH)D levels are closely related to neonatal sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the classic regulation of calcium and phosphorus metabolism, when combined with VDR, vitamin D can also inhibit proliferation, promote differentiation, regulate immunity, inhibit cell necrosis, inhibit tumor infiltration and metastasis, and other non-calcium regulatory effects. [21][22][23] In this study, we found that the serum 25(OH)D level of patients with sepsis was significantly lower than that of the control group, and the VDR rs739837 G > T allelic variation was correlated with the increase of serum 25(OH)D. Küchler et al 24 with sepsis and bronchial bubble lavage fluid of patients with pneumonia, sTREM-1 is significantly increased. 30 In this study, we found that the serum sTREM-1 level of neonatal sepsis was significantly higher than that of the control group.…”
Section: Discussionsupporting
confidence: 47%
“…These results are in line with a recently published systematic review and meta-analysis concluding that periodontitis is associated with lower 25OHD levels [15]. This concurs with the known bone-protective effect of higher 25OHD levels, which have been shown to decrease the ratio of RANKL to OPG expression by periodontal ligament fibroblasts controlling osteoclastogenesis [60]. Ketharanathan et al focused on radiographic bone loss in their cohort study to investigate the impact of 25OHD levels in periodontitis patients.…”
Section: Discussionsupporting
confidence: 72%
“…Even though this situation would not necessarily occur in vivo, this could explain why ff subjects for rs2228570, associated with higher vitamin D levels, would show more external apical root resorption during orthodontic treatment. Besides, it was shown that other SNPs in VDR influence VDR mRNA expression under conditions of simulated pressure and 25(OH)D 3 supply [54]. These findings would provide new insights into the molecular mechanisms of how SNPs in VDR would influence the amount of external apical root resorption related to orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%